Faster Decoding of rank metric convolutional codes - Napp, Diego (2018)
A new construction of maximum rank distance systematic rank metric convolutional codes is presented, which permits to reduce the computational complexity of the decoding procedure, i.e., of the underlying Viterbi algorithm. This result is achieved by lowering the number of branch metrics to be calculated and by setting to the highest value the metric of the remaining edges in the trellis.